DIAGNOSIS, PROPHYLAXIS AND TREATMENT OF CHRONIC CATARRHAL GINGIVITIS IN CHILDREN WITH DISABILITIES IMPROVEMENT - Yo.Q. Eronov; F.L. Mirsalixova (Scholar Express Journal, 2021)
Prevention and effective treatment of dental diseases in children with cerebral palsy is one of the most urgent problems. In children with this pathology, the development of special therapeutic measures is important. Cerebral palsy is a complex disease of the nervous system that occurs in the conditions of the maturity of the cerebral apparatus, that is, the development of the fetus, childbirth and the newborn (Nikitina V. V., 1979) Cerebral palsy is characterized by damage to the musculoskeletal system, speech and mental disorders, decreased hearing and vision.The symptoms of the first Marotaba cerebral palsy were described by the English surgeon William Little in 1861; at the beginning of the 20th century, Muratova A. S. (1898); it shows the main clinical signs of cerebral palaxia. The term "cerebral palsy" was approved by a group of international scientists in Oxford in 1958.
Keywords: Cerebral Palsy; Dental Diseases; effective; dental